IMPLEMENTASI METODE UMMI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI MIN 2 JOMBANG - ike nur filiatil (JoEMS (Journal of Education and Management Studies), 2020)
Ummi method is a method that introduces how to read Al-Quraysh with tartil. In learning the Ummi method uses an approach. That approach is the mother tongue approach. There are 3 strategies for this approach, they are: Direct method, Repetition, Affection. The research objectives to be achieved in this study are (1) How to implement the Ummi method in MIN 2 Jombang (2) How to improve the ability to read the Qur'an in MIN 2 Jombang. (3) What are the supporting and inhibiting factors. To achieve the above objectives, researchers use qualitative research types. This research uses descriptive qualitative approach and data collection techniques in the form of observation methods, interview methods, and documentation. While the data analysis technique used by researchers is to use data reduction, data presentation, then drawing conclusions. From the results of data analysis about the implementation of the Ummi method in improving the ability to read the Qur'an in MIN 2 Jombang, several things are carried out, namely: learning is carried out 4 times in 1 week 8 hours of learning, one teacher is maximum of 15 students, with 60 minutes using a private learning model individual, classical individual, classical aca see, classical read pure listening. By using 7 stages of learning, i.e., opening, apperception, concept planting, concept understanding, skills / training, evaluation, and closing. The improvement of the implementation of the Ummi Min 2 Jombang method is very good, it can be seen from the ability of students in reading the Qur'an very well, reading it has begun with tarti, and reading it in accordance with the principles of tajwid science, and there are also those who follow tartil competitions at the district level and get a champion. Supporting factors consist of madrasa support, Al-Qur'an teachers, parents, and infrastructure such as volumes, visuals, and achievement books. While the inhibiting factors are the students feel they can and underestimate the material, and the lack of administrative completeness.